2018
DOI: 10.1093/infdis/jiy721
|View full text |Cite
|
Sign up to set email alerts
|

AS03-Adjuvanted H5N1 Avian Influenza Vaccine Modulates Early Innate Immune Signatures in Human Peripheral Blood Mononuclear Cells

Abstract: Background. Adjuvant System 03 (AS03) markedly enhances responses to influenza A/H5N1 vaccines, but the mechanisms of this enhancement are incompletely understood. Methods. Using ribonucleic acid sequencing on peripheral blood mononuclear cells (PBMCs) from AS03-adjuvanted and unadjuvanted inactivated H5N1 vaccine recipients, we identified differentially expressed genes, enriched pathways, and genes that correlated with serologic responses. We compared bulk PBMC findings with our previously published assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
5
17
0
Order By: Relevance
“…Although only the 3.75 µg dose level of CoVLP was used in the Phase study, data from the Phase 1 trial that included groups given unadjuvanted CoVLP at three dose levels (3.75, 7.5 and 15µg/dose) showed that local and systemic reactogenicity was higher in adjuvanted groups as compared to non-adjuvanted groups, as would be expected from its use with other antigens 25,33,34 . As expected 26 and has been observed for mRNA, adenovirus vector, inactivated virus, and recombinant protein-based COVID-19 vaccines [35][36][37][38][39][40][41][42] reduced reactogenicity was observed in the older adults. The safety profile in the Older Adults was consistent with the safety profile in the Adult population no new safety concerns were reported relative to our phase 1 study, suggesting that CoVLP+AS03 is well-tolerated in healthy individuals 18 years of age and older.…”
Section: Discussionsupporting
confidence: 76%
“…Although only the 3.75 µg dose level of CoVLP was used in the Phase study, data from the Phase 1 trial that included groups given unadjuvanted CoVLP at three dose levels (3.75, 7.5 and 15µg/dose) showed that local and systemic reactogenicity was higher in adjuvanted groups as compared to non-adjuvanted groups, as would be expected from its use with other antigens 25,33,34 . As expected 26 and has been observed for mRNA, adenovirus vector, inactivated virus, and recombinant protein-based COVID-19 vaccines [35][36][37][38][39][40][41][42] reduced reactogenicity was observed in the older adults. The safety profile in the Older Adults was consistent with the safety profile in the Adult population no new safety concerns were reported relative to our phase 1 study, suggesting that CoVLP+AS03 is well-tolerated in healthy individuals 18 years of age and older.…”
Section: Discussionsupporting
confidence: 76%
“…Three other genes correlated with antibody responses at this timepoint and are known to be induced by IFN-γ signaling: STAT1 (transcription factor for interferon inducible genes), IFIT1 and IFIT2 (proteins that inhibit expression of viral messenger RNA [32]). STAT1 also predicts delayed antibody responses in other vaccine studies [33,34].…”
Section: Discussionmentioning
confidence: 86%
“…A critical question for the field of vaccinology is whether metabolite profiles can predict the downstream cellular and/or adaptive responses that are fundamental to immunological protection against pathogens. Here, we employed elastic net regularized linear regression, which was successfully applied to similar contexts [ 7 , 8 ], to test metabolites as predictors of antibody response (peak tularemia-specific microagglutination titer) or peak CD4+ and CD8+ T cell activation. The input set included log 2 -fold changes for all metabolites that were in the final analysis dataset (3741 C18 and 6562 for HILIC).…”
Section: Resultsmentioning
confidence: 99%
“…The application of high-throughput technologies to assess cell-wide changes in gene expression, protein abundance, small molecules, and lipids opens a new opportunity to better understand the mechanisms of vaccines and human immune responses [ 3 , 4 , 5 , 6 , 7 , 8 ]. For example, transcriptomics studies to assess changes in gene expression in PBMCs or individual cell types revealed detailed information on immune signaling pathway activation following vaccination against H5N1 influenza when given with AS03 vaccine adjuvant and identified early markers that correlated with later protection [ 7 , 8 ]. Metabolomics measures global metabolite profiles, reflecting both cellular metabolism and systemic metabolite signals [ 9 , 10 ] and similarly promises to reveal biomarkers that correlate with vaccine protection or other phenotypes of interest.…”
Section: Introductionmentioning
confidence: 99%